Implementasi Teknologi Penghangat Minuman Berbasis Termo Digital Kepada Pemilik Warung Kopi di Desa Banjarsari - Moh Anshori Aris Widya; Nurul Yaqin; Nur Khafidhoh; Tholib Hariono (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
The purpose of service here is to overcome the problems faced by partners, then the implementation of beverage warmer technology has the following objectives: First, to provide ideas to utilize affordable goods into goods that have more value to meet economic needs. Methods for implementing community service activities include lecture, discussion, and workshop (training) methods. The results of this service include, the people of Banjarsari Village are very enthusiastic about the implementation of this drink warmer technology, because before they have never heard of this drink warmer technology, their lack of knowledge about the tools used makes the people of Banjarsari Village anticipated by making a guide regarding It is hoped that this tool can help improve the economy of the residents of Banjarsari Village, and make it easier for them to warm their cold drinks so they are delicious to enjoy